Design of experiments (DoE) to develop and to optimize nanoparticles as drug delivery systems - Tavares Luiz, Marcela; Santos Rosa Viegas, Juliana; Palma Abriata, Juliana; Viegas, Felipe; Testa Moura de Carvalho Vicentini, Fabiana; Lopes Badra Bentley, Maria Vitória; Chorilli, Marlus [UNESP]; Maldonado Marchetti, Juliana; Tapia-Blácido, Delia Rita (Elsevier, 2021)
Nanotechnology has been widely applied to develop drug delivery systems to improve therapeutic performance. The effectiveness of these systems is intrinsically related to their physicochemical properties, so their biological responses are highly susceptible to factors such as the type and quantity of each material that is employed in their synthesis and to the method that is used to produce them. In this context, quality-oriented manufacturing of nanoparticles has been an important strategy to understand and to optimize the factors involved in their production. For this purpose, Design of Experiment (DoE) tools have been applied to obtain enough knowledge about the process and hence achieve high-quality products. This review aims to set up the bases to implement DoE as a strategy to improve the manufacture of nanocarriers and to discuss the main factors involved in the production of the most common nanocarriers employed in the pharmaceutical field.
Keywords: Box-Behnken Design; Central Composite Design; Fractional Factorial Design; Full Factorial Design; Nanomedicine; Nanotechnology; Plackett-Burman Design; Quality by Design; Response Surface Methodology